The Importance of the Georgian Translations of "The Ladder of Divine Ascent" by John Climacus for Georgian and Byzantine Philology - Makaradze, Irma (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2016)
The aim of the present article is to represent the importance of Georgian translations of The Ladder of Divine Ascent by John Climacus through analisis of various literary issues for Byzantine and Georgian philology.